Fatty acid profile of various fresh water and marine fishes at different geographical locations. / Tengku Nurul Diyana Tg Zainal Alam Shah - Tg Zainal Alam Shah, Tengku Nurul Diyana (Faculty Of Applied Sciences, 2017)
The comparison on the fatty acid compositions of one marine fishes Rastrelliger kanagurta and one freshwater fish Monopterus albus in two different locations which is Kelantan and Pahang with different environmental factor were studied. Result showed that the lipid content of Monopterus albus is 8.36% in Kelantan and 0.84% in Pahang. Whereas, lipid content of Rastrelliger kanagurta is 9.69%in Kelantan 1.60% in Pahang. In the fatty acid analysis, it was discovered that the major fatty acid in the oil from the Rastrelliger kanagurta, between Kelantan and Pahang recorded the highest PUFA specifically DHA and EPA regarding to nutritional aspect with 48.51% and 48.33% followed by freshwater species, Monopterus albus (eel) members between Kelantan and Pahang with 13.32% and 6.32% respectively